2001
DOI: 10.1016/s0168-6496(01)00153-2
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous iron oxidation by denitrifying bacteria in profundal sediments of a deep lake (Lake Constance)

Abstract: Profundal sediments of Lake Constance were sampled at 60^130 m water depth and studied with respect to the population sizes and depth distribution of mixotrophic and lithotrophic iron-oxidizing, denitrifying bacteria. The sediment cores showed a distinct stratification with oxygen and nitrate being consumed within the first centimeter of the sediment. The sediment contained large amounts of acid-extractable iron (0.8^1.4% of the dry mass). The proportion of ferrous iron in the solid phase increased dramaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
(35 reference statements)
2
29
0
Order By: Relevance
“…This is due to nitrate's higher energetic efficiency as an electron acceptor than iron (e.g., Hansen et al 2003;Parsons et al 2017); as nitrate must be consumed prior to the onset of iron reduction (Reed et al 2011), longer periods of anoxia are required to cause release of iron-bound P. Second, heterotrophic nitrate reduction (denitrification) coupled to the oxidation of organic matter may deplete the sediment of labile organic matter, decreasing the probability, or rate, of reductive dissolution of iron oxyhydroxides at greater sediment depth due to electron donor limitation. Third, nitrate reduction can be coupled directly to the oxidation of upward-diffusing iron(II) from more reduced sediments (e.g., Straub et al 1996;Hauck et al 2001;Melton et al 2012). This can result in the precipitation of iron(III) oxyhydroxides below the oxic zone in sediments, providing a greater barrier to upwarddiffusing P, which can decrease or prevent internal P loading.…”
Section: Nitrate Concentrations In Surface Watermentioning
confidence: 99%
“…This is due to nitrate's higher energetic efficiency as an electron acceptor than iron (e.g., Hansen et al 2003;Parsons et al 2017); as nitrate must be consumed prior to the onset of iron reduction (Reed et al 2011), longer periods of anoxia are required to cause release of iron-bound P. Second, heterotrophic nitrate reduction (denitrification) coupled to the oxidation of organic matter may deplete the sediment of labile organic matter, decreasing the probability, or rate, of reductive dissolution of iron oxyhydroxides at greater sediment depth due to electron donor limitation. Third, nitrate reduction can be coupled directly to the oxidation of upward-diffusing iron(II) from more reduced sediments (e.g., Straub et al 1996;Hauck et al 2001;Melton et al 2012). This can result in the precipitation of iron(III) oxyhydroxides below the oxic zone in sediments, providing a greater barrier to upwarddiffusing P, which can decrease or prevent internal P loading.…”
Section: Nitrate Concentrations In Surface Watermentioning
confidence: 99%
“…Chemolithotrophic nitrate-dependent Fe(II) oxidation was first reported by Straub et al, (1996) and has been reported in various environments since, primarily in lake sediments (Straub and BuchholzCleven, 1998;Hauck et al, 2001;Muehe et al, 2009). Although autotrophic nitrate-dependent oxidation of Fe(II) was observed in many natural habitats, to date there are only two pure cultures available: the hyperthermophilic archaeon Ferroglobus placidus (Hafenbradl et al, 1996) and the betaproteobacterium Pseudogulbenkiania sp.…”
Section: Introductionmentioning
confidence: 96%
“…For example, the nitrate plume could affect the redox conditions (initially reducing) of the host rock in the vicinity of the repository due to microbial nitrate reduction using clay components (e.g. organic matter, pyrite or other Fe(II)-containing minerals) as electron donor (Hauck et al 2001;Jørgensen et al 2009;Mariën et al 2011;Zhang et al 2012Zhang et al , 2013. As the reducing capacity of the undisturbed clay formation will strongly impact the speciation, the solubility, the retention and the transport properties of redox-sensitive radionuclides (Se, Tc, U, Np, Pu, etc.…”
Section: Introductionmentioning
confidence: 99%